(untitled) (Decentering European studies: perspectives on Europe from its beyond, 2025)
This chapter compares how the German and Chinese healthcare systems differed in their impact on poverty risk among low-income people during the COVID-19 pandemic. It examines how long-term care policy in these two countries can support the population from such risk during pandemics, arguing that the interplay of healthcare and long-term care policy with regard to eligibility for and access to benefits is crucial to protect low-income individuals from the risk of falling into poverty.